Macrofauna as a major driver of bentho‐pelagic exchange in the southern North Sea. Issue 6 (6th May 2021) - Neumann, Andreas; van Beusekom, Justus E. E.; Eisele, Annika; Emeis, Kay‐Christian; Friedrich, Jana; Kröncke, Ingrid; Logemann, Ella Lu; Meyer, Julia; Naderipour, Céline; Schückel, Ulrike; Wrede, Alexa; Zettler, Michael L.
Abstract: The contribution of sediments to nutrient cycling of the coastal North Sea is strongly controlled by the intensity of fluxes across the sediment water interface. Pore‐water advection is one major exchange mechanism that is well described by models, as it is determined by physical parameters. In contrast, biotransport (i.e., bioirrigation, bioturbation) as the other major transport mechanism is much more complex. Observational data reflecting biotransport, from the German Bight for example, is scarce. We sampled the major sediment provinces of the German Bight repeatedly over the years from 2013 to 2019. By employing ex situ whole core incubations, we established the seasonal and spatial variability of macrofauna‐sustained benthic fluxes of oxygen and nutrients. A multivariate, partial least squares analysis identified faunal activity, in specifically bioturbation and bioirrigation, alongside temperature, as the most important drivers of oxygen and nutrient fluxes. Their combined effect explained 63% of the observed variability in oxygen fluxes, and 36–48% of variability in nutrient fluxes. Additional 10% of the observed variability of fluxes were explained by sediment type and the availability of plankton biomass. Based on our extrapolation by sediment provinces, we conclude that pore‐water advection and macrofaunal activity contributed equally to the total benthic oxygen uptake in the German Bight.